2020
DOI: 10.1017/s0007114520001634
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to complementary feeding in the first year of life and risk of overweight at 24 months of age: changes from 2004 to 2015 Pelotas (Brazil) Birth Cohorts

Abstract: Complementary feeding (CF) and overweight relationships during early childhood are inconsistent in the literature. We described the association of CF during the first year of life with risk of overweight at 24 months of age in the population-based 2004 and 2015 Pelotas (Brazil) Birth Cohorts (2004c and 2015c). CF introduction was evaluated at the 3 and 12 months’ follow-ups by asking mothers using a list of foods. Risk of overweight at 24 months of age was BMI-for-age z-score above +1sd from the median of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Several national and international studies have found association between economic indicators and early introduction of fluids and other types of food. 3,4,22 Such an early introduction may be associated with women's lower access to information about healthy eating practices and with their slight difficulty in reading and understanding educational materials provided by the health services. 23 It was also suggested that the lack of knowledge in association with low socioeconomic level, makes several mothers see teas as natural remedies; consequently, they attribute important functions to them, such as mitigating infantile colic and gas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several national and international studies have found association between economic indicators and early introduction of fluids and other types of food. 3,4,22 Such an early introduction may be associated with women's lower access to information about healthy eating practices and with their slight difficulty in reading and understanding educational materials provided by the health services. 23 It was also suggested that the lack of knowledge in association with low socioeconomic level, makes several mothers see teas as natural remedies; consequently, they attribute important functions to them, such as mitigating infantile colic and gas.…”
Section: Resultsmentioning
confidence: 99%
“…27 The aim of this present study was to investigate factors associated with early tea introduction in children's diet in their first month of life. Despite the high prevalence of tea consumption among newborns in the country, 4,6,18,19,28 studies available in the literature about factors exclusively associated with tea consumption remain scarce and are old. 3,12 This fact emphasizes the importance of this current study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adequate complementary feeding practices (CFP) during the first 2 years of life are key to proper infant growth, nutrition, and development. During the first year of life, BF and CF coincide with a period of behavioral modeling which determine longterm eating habits, growth, and development outcomes, as well as future metabolic responses linked to non-communicable diseases like type 2 diabetes (1).…”
Section: Introductionmentioning
confidence: 99%